Animals and Emotions in Medieval German Literature: The Various Functions of Bestial Imagery in the Staging of Emotions - Hofert, Sandra (Aestimatio)

(untitled) (Institute for Research in Classical Philosophy and Science, 2022)
This article, which continues ideas developed in the context of the Deutsche Forschungsgemeinschaft: Graduiertenkolleg 1876—215342465 (GRK1876), examines how animals are used in medieval texts to (re)present, shape, and develop the literary representation of emotions. On the basis of selected examples, it shows how diverse the literary functions of animal imagery can be and how many different poetic and aesthetic strategies can be found for staging animals, connecting them with human characters and the recipients of the tale. In this way, animals can serve as objects of cultural self-reflection and as models for philosophical orientation.